Temporal development of ozone within the Arctic Vortex during the winter of 1991/92 - Braathen, Geir O.; Rummukainen, Markku ; 0000-0001-5709-9804; Kyrö, Esko; Schmidt, Ulrich; Dahlback, Arne; Jørgensen, Torben S.; Fabian, Rolf; Rudakov, Vladimir V.; Gil, Manuel; Borchers, Reinhardt (Geophysical Research Letters, 1994)
In this study we address the question of temporal ozone trends on isentropic surfaces within the Arctic polar vortex during EASOE. We have combined ozone sonde data from twelve campaign stations distributed throughout the European sector of the Arctic. The development of ozone at the 425, 475, 550 and 700K levels is presented, using analysed fields of isentropic potential vorticity and isentropic back‐trajectories to separate inner vortex air from air staying outside the vortex. Vertical N2O profiles measured in Kiruna have been used to obtain information on the vertical movement of the polar air mass. Elimination of effects due to diabatic descent leads to a weak, yet significant, chemically induced loss of ozone at 475 K. At 425 K we observe a negative trend in the ozone mixing ratio, but for this level it has not been possible to assess the influence of subsidence. Heterogeneous chemistry on aerosols of volcanic origin from the eruption of Mt. Pinatubo might have contributed to the negative ozone trends.